Impact of Ho3+-doping on 13C dynamic nuclear polarization using trityl OX063 free radical. Issue 31 (18th July 2016) - Kiswandhi, Andhika; Niedbalski, Peter; Parish, Christopher; Kaur, Pavanjeet; Martins, André; Fidelino, Leila; Khemtong, Chalermchai; Song, Likai; Sherry, A. Dean; Lumata, Lloyd
Abstract : We have investigated the effects of Ho-DOTA doping on the dynamic nuclear polarization (DNP) of [1- 13 C] sodium acetate using trityl OX063 free radical at 3.35 T and 1.2 K. Abstract : We have investigated the effects of Ho-DOTA doping on the dynamic nuclear polarization (DNP) of [1- 13 C] sodium acetate using trityl OX063 free radical at 3.35 T and 1.2 K. Our results indicate that addition of 2 mM Ho-DOTA on 3 M [1- 13 C] sodium acetate sample in 1 : 1 v/v glycerol : water with 15 mM trityl OX063 improves the DNP-enhanced 13 C solid-state nuclear polarization by a factor of around 2.7-fold. Similar to the Gd 3+ doping effect on 13 C DNP, the locations of the positive and negative 13 C maximum polarization peaks in the 13 C microwave DNP sweep are shifted towards each other with the addition of Ho-DOTA on the DNP sample. W-band electron spin resonance (ESR) studies have revealed that while the shape and linewidth of the trityl OX063 ESR spectrum was not affected by Ho 3+ -doping, the electron spin–lattice relaxation time T 1 of trityl OX063 was prominently reduced at cryogenic temperatures. The reduction of trityl OX063 electron T 1 by Ho-doping is linked to the 13 C DNP improvement in light of the thermodynamic picture of DNP. Moreover, the presence of Ho-DOTA in the dissolution liquid at room temperature has negligible reduction effect on liquid-state 13 C T 1, in contrast to Gd 3+ -doping which drastically reduces the 13 C T 1 . The results here suggest that Ho 3+ -doping is advantageous over Gd 3+ in terms of preservation of hyperpolarized state—an important aspect to consider for in vitro and in vivo NMR or imaging (MRI) experiments where a considerable preparation time is needed to administer the hyperpolarized 13 C liquid.